Investigation On The Breakdown Characteristics Of Nitrogen And Oxygen Gas Mixtures Under Standard Lightning Impulse - Sa'id, Ummi Hamizah; Kamarudin, Muhammad Saufi (Evolution in Electrical and Electronic Engineering, 2023)
This paper is concerned about the potential for sulphur hexafluoride (SF6) to contribute to global warming; therefore, it is necessary to find another gas to replace SF6 as the gas insulator in high voltage applications. To determine the best gas insulator for insulation properties, the breakdown characteristics of N2 and O2 gas mixtures, pure N2 gas, and pure O2 gas were analyzed by applying a lightning impulse, varying the gap distance between the sphere and plate electrodes, and varying the mixing ratio of these gases at the same pressure (1 bar). Up and Down method is used to measure the breakdown voltage to obtain 50% of the breakdown voltage, U50 from breakdown testing according to the BS EN 60060-1 standard. For all gas insulators, U50 increases with electrode distance. Simulations from FEMM software show that Emax decreases with electrode gap length. As maximum electric field, Emax decreases, the field utilization factor decreases, showing that electrode configuration uniformity diminishes with gap distance. Based on the results obtained, N2 gas was discovered to be one of the most effective insulators as a secondary gas compared to O2 gas and gas mixtures between N2 and O2 gas because it has the highest breakdown voltage values, 37.415 kV as compared to 34.123 kV (N2+ O2 gas) and 20.730 kV (O2 gas). Based on this study, pressure variations could be made as insulating properties can be accurately identified by using gas chamber pressure and rising pressure increases gas mixture breakdown strength.